Privacy Proliferation of Customized Web Search Engine - Arunachalam, N; Radjou, S; Aravindan, P; Sivagurunathan, T (International Journal of Engineering and Technology, 2018)
In last few years the illegal disclosure of user privacy in web search engine has become more serious. Protecting and Pre-venting user privacy from illegal disclosure is attracting the interest among researchers in recent times. Existing web search engines do not consider the privacy of the users. Search engines tend to collect all the information from the user. A system to ensure the privacy of the user is essential. Hence, the Personalized Web Search (PWS) method was put forward to take control over the amount of information that the user can provide to the search engines. This PWS provides privacy protec-tion in web search system and minimize the information disclosure of the user related to privacy through a customizable web-search.Â Â